Transformation Of Learner Learning: Improving Reasoning Skills Through Artificial Intelligence (AI) - Susanto, Susanto; Andrianingsih, Ayu; Sutawan, Komang; Vike Aprilianin Marwintaria; Ria Astika (Journal of Education, Religious, and Instructions (JoERI), 2023)
The research aims to explore the potential of artificial intelligence (AI) in the context of Learning as a solution to the challenges in developing thinking skills. Through the use of AI technology, the study focuses on finding out the relationship between AI and students' ability to argue. The approach used in this research is quantitative with correlational methods. Research results show that AI in learning can be a significant catalyst for the development of critical and analytical thinking skills. Students engaged in learning environments using AI showed an improvement in problem-solving, information-analysis, and critical thinking skills so that their ability to argue improved. In addition, learning efficiency, and motivates the learners to reach their maximum potential. This research contributes to an understanding of how AI in education can have a positive impact on the development of argumentation skills. The practical implications of these findings can open the door to the development of more effective and personalized learning strategies in the future, creating a responsive and adaptive educational environment.